A Penguatan Kelembagaan Lokal dan Konservasi Ekologi Mangrove Jangkaran Untuk Pariwisata Berkelanjutan - Budisusila, Antonius; Tri Priantoro , Antonius; Bambang Harnoto , Laurentius (Jurnal Atma Inovasia, 2024)
This community service focuses on strengthening local institutions, preserving mangrove ecology and increasing tourist visits. Activities are carried out through collective problem solving, training and mentoring. This community service has succeeded in encouraging and implementing pro-sustainable tourism policies. Strengthening informal institutions, especially developing joint agreements, resolving disputes/conflicts, cooperation, commitment and new ideas, namely low carbon tourism. This activity also ensures that all sustainable tourism ideas are prepared, included and regulated in the review and revision of the Jangkaran Village Tourism Master Plan (RIPPARKAL). Ripparkal is the foundation for mangrove ecology and ecosystem conservation through village regulations as formal institutional strengthening. In this way, the institution is legal and binding, so that the government provides the village budget and infrastructure to carry it out. Apart from that, focusing on ecological conservation can encourage carbon trading from communities to emitters as an alternative financing mechanism in line with Presidential Regulation No. 98/2021. However, this dedication is too early to evaluate the achievement of ecological and environmental improvements, as well as overcoming decline. visits for short periods of service. This still requires assistance and capacity strengthening to fulfill the necessary requirements and complementary requirements to enter the next carbon trading system.